Phenotyping pipeline reveals major seedling root growth QTL in hexaploid wheat - Atkinson, Jonathan A.; Wingen, Luzie U.; Griffiths, Marcus; Pound, Michael P.; Gaju, Oorbessy; Foulkes, John; Le Gouis, Jacques; Griffiths, Simon; Bennett, Malcolm J.; King, Julie; Wells, Darren M. (Oxford University Press, 2015)
Seedling root traits of wheat (Triticum aestivum L.) have been shown to be important for efficient establishment and linked to mature plant traits such as height and yield. A root phenotyping pipeline, consisting of a germination paper-based screen combined with image segmentation and analysis software, was developed and used to characterize seedling traits in 94 doubled haploid progeny derived from a cross between the winter wheat cultivars Rialto and Savannah. Field experiments were conducted to measure mature plant height, grain yield, and nitrogen (N) uptake in three sites over 2 years. In total, 29 quantitative trait loci (QTLs) for seedling root traits were identified. Two QTLs for grain yield and N uptake co-localize with root QTLs on chromosomes 2B and 7D, respectively. Of the 29 root QTLs identified, 11 were found to co-localize on 6D, with four of these achieving highly significant logarithm of odds scores (>20). These results suggest the presence of a major-effect gene regulating seedling root vigour/growth on chromosome 6D.